(Des)venturas de um professor com os jogos esportivos coletivos como prática pedagógica para o ensino do futebol na escola - Ribeiro, Valdione dos Santos (2023)
Football is the sport that gains greater prominence in brazilian society and, consequently, in school Physical Education. Thinking about teaching football as a school content is to reflect on its presence in classes beyond simply playing ball and for that, new methodological proposals should be used. With that in mind, this work aims to explore a pedagogical practice based on games that allows expanding the development of football culture in the school context, problematizing and reflecting on teaching in a way that opposes traditional models of sports education. Using the action research approach, where all the actors involved in the process seek alternatives to solve the problems encountered, the pedagogical proposal explored is the Collective Sports Games (JEC), which uses games that involve students in problem situations that are encountered during a football match, problems that must be understood and thought about collectively in order to obtain a solution without, however, harming individuality, that is, the individual helping the collective. The results found in the research universe were satisfactory, since the development of tactical/technical skills was noticeable in the students; with regard to social issues, the debates held, if not causing immediate changes, were able to provide reflections on issues that were not even noticed by students before. In conclusion, it was identified that the methodological proposal for teaching football through the JEC proved to be effective in the universe of research and that it can be an alternative for any teacher who intends to teach sports content in classes beyond traditional methods.